Partisipasi Umat dalam Pelayanan Pastoral Bagi Kuam Lansia di Stasi Santa Maria Perigiq - Supiana; Nikolaus Anggal; Gervasius Panggur Masuri (Gaudium Vestrum - Jurnal Kateketik Pastoral, 2017)
The empirical data showed that there were no special pastoral services in the forms of either sacramental service, catechesis service, or prayer gathering service for the elderly. However, the participation takes place beyond the above-mentioned pastoral services, in the forms of taking responsibility and providing services for the elderly in respective neighborhood, by caring, treating and paying proper attention to the elderly in each household. The themes appeared related to the focus of the study, after being grouped and categorized, were mostly related to participation of the Catholics, pastoral services, the elderly situation and condition, and the local community’s tradition. The results of the inter-categories relationship analysis show that the Catholics participation in the services provided for the elderly does not depend on whether there are special pastoral services provided by the Church for the elderly or not. The Catholics participation does not depend either on the situation and condition faced by the elderly. The participation runs naturally based on the local community’s tradition and cultural values. Therefore, the participation of the Catholics in the pastoral service for the elderly at the Santa Maria Church-station, Perigiq is still apparently in the form of traditional participation, based on the tradition and culture of the local community.